Domestic Waste Management Through The Waste Bank Program in Pasirlawang Village Purwadadi District Ciamis Regency - Afriany, Trisna; Yani Sri Astuti (Universitas Negeri Surabaya, 2025)
Suboptimal waste management resulted in environmental hygiene problems in Pasirlawang Village, Purwadadi District, Ciamis Regency. In 2021, there is one effort to overcome this problem, namely by establishing a waste bank. The purpose of this study is to find out domestic waste management activities through the waste bank program on environmental cleanliness and to find out the benefits resulting from the existence of a waste bank for the community in Pasirlawang Village. The research method used is quantitative descriptive. The results of the study show that domestic waste management activities through the waste bank program for environmental cleanliness include waste sorting carried out by members by providing waste containers for organic and inorganic waste, depositing waste whose time changes no longer according to the initial agreement, weighing waste of one to more than five kilograms each time depositing, recording later the amount of money received can be taken directly or stored in the passbook, waste transportation is carried out by the manager to each member's house who cannot deposit their waste directly to the waste bank location, and the use of waste by members including organic waste is used as animal feed and ecoenzymes. As for inorganic waste, it is made by handicrafts or used according to the same/different functions.